Local Recurrence Rates of Malignant Melanoma After Mohs Micrographic Surgery Are Lowest With 5- to 10-mm Initial Margins: A Systematic Review and Meta-Analysis. Issue 2 (19th February 2023) - Campbell, Elliott H.; Crum, Olivia M.; Chelf, Cynthia J.; Demer, Addison M.; Brewer, Jerry D.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Current consensus guidelines have discouraged the use of sub-0.5-cm (in situ) and sub-1-cm (invasive) margins when performing Mohs micrographic surgery (Mohs) for melanoma, with minimal evidence to guide this recommendation. OBJECTIVE: To compare melanoma local recurrence rates after Mohs based on initial margin size. MATERIALS AND METHODS: A systematic review and meta-analysis was conducted with search terms including Mohs micrographic surgery, surgical margin, recurrent disease, and melanoma. RESULTS: Forty-three studies were included. The 5- to 10-mm margin category had a statistically significant lower local recurrence compared with 1- to 5-mm and 5-mm categories. Recurrence for 1- to 5-mm, 5-mm, 5- to 10-mm, and 10-mm categories were 2.3% (CI 0.8–3.5, p < .001), 1.4% (CI 0.6–2.2, p < .001), 0.3% (CI 0.2–0.5, p < .001), and 6.1% (CI -6.7 - 18.8, p = .349), respectively. Number of stages for 1 to 5, 5, 5 to 10, and 10-mm categories were 1.8, 1.8, 1.6, and 1.6, respectively. There was no statistically significant difference between the groups ( p = .694). CONCLUSION: Five- to 10-mm margins were associated with the lowest local recurrence rates. A 5- to 10-mm initial margin should be considered where other factors (tumor characteristics, anatomical or functional considerations) allow.